Inhibition of a DNA Polymerase from Bacillus subtilis by Hydroxyphenylazopyrimidines - Gass, Kenneth B. (1973)
The antimicrobial agent, 6-(p-hydroxyphenylazo)-uracil, specifically inhibits DNA polymerase III of Bacillus subtilis with a K(i) of less than 1 μM. The inhibition requires prior reduction of the drug, is reversible, and is competitive with dGTP. High amounts of dATP prevent inhibition by the closely related drug, 6-(p-hydroxyphenylazo)-isocytosine. A model is presented in which the inhibitors base-pair with the template while part of a ternary complex with the enzyme. These results imply that DNA polymerase III of B. subtilis is necessary for chromosomal replication.